Pengaruh Pemberian Ekstrak Etanol Daun Sambiloto Andrographis paniculata (Burm. fil) Ness Terhadap Histologi dan Faal Ginjal Tikus Putih (Rattus novergicus L.) yang Diinduksi Timbal Asetat (Pb(C2H3O2)2) - Cutami, Ledia Fristia; Tambunan, Efrida Pima Sari; Febriani, Husnarika (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This study aims to examine the impact of ethanol extract from bitter leaf (Andrographis paniculata) on the morphology, histology, and physiology of the kidneys of white rats (Rattus novergicus) induced by lead acetate. The method used was a completely randomized experimental design, consisting of five treatment groups with five repetitions. The control group was only given food and drink, while the experimental group received lead acetate for 28 days at a dose of 40 mg, followed by administration of bitter extract at varying doses (250, 500, and 750 mg/kg body weight) for 14 days. The results showed that administration of lead acetate caused histological damage to the kidneys, such as necrosis, tubular degeneration, and tubular dilatation, and increased blood urea and creatinine levels, which are indicators of kidney function. These findings indicate that an ethanol extract of bitter leaf at a dose of 750 mg/kg body weight can mitigate this histological damage and has the potential to reduce urea and creatinine levels. Thus, bitter leaf extract shows potential as a kidney protective agent against damage induced by lead acetate. Keywords: Kidney, Creatinine, Lead Acetate, Ureum